Update on the management of peripheral arterial disease (PAD) - Liew, Ngoh Chin; Moissinac, Kevin; Lee, Limi; Gee, Tikfu; Raja Zezeman, Raja Badrul Hisham (Malaysian Medical Association, 2011)
There has been much progress made in the management of peripheral arterial disease (PAD) in the past two decades. Progress in the understanding of the endothelial-platelet interaction during health and disease state have resulted in better antiplatelet drugs that can prevent platelet aggregation, activation and thrombosis during angioplasty and stenting. Collaborative effort by different international societies has resulted in a consensus guideline that recommends the modality of intervention in certain disease states. Progress in perioperative care has reduced the morbidity and mortality associated with peripheral vascular reconstruction surgery. Nevertheless, the advances in percutaneous peripheral intervention (PPI) have made a paradigm shift in the current management of patients. The procedure is safe and effective and is emerging as the first choice revascularization procedure.